RANCANG BANGUN APLIKASI GAME EDUKASI OPERASI HITUNG BERBASIS GAMIFIKASI UNTUK SISWA SMP - Fadil Julianto; Sidhiq Andriyanto; Better Swengky (KHARISMA Tech, 2026)
This study aims to develop a gamification-based educational game application that supports learning arithmetic operations for junior high school students. The application was developed through several stages, including needs analysis, system design using an Activity Diagram, implementation using Flutter and Laravel, and evaluation through Black Box Testing and User Acceptance Testing (UAT). The application integrates structured learning materials, interactive quizzes, and an educational Snakes and Ladders Math Game designed to enhance students’ motivation and conceptual understanding. The Black Box Testing results indicate that all system functions operate properly and as intended. Meanwhile, the UAT results involving 18 seventh-grade students achieved an average feasibility score of 88.51%, categorized as highly feasible. The highest score was obtained in the game responsiveness aspect, demonstrating that the application provides a smooth and engaging learning experience. Overall, this application is considered effective as an alternative digital learning media that improves students’ understanding of arithmetic operations and supports the digitalization of mathematics learning in junior high schools.